Sistem Informasi Manajemen : Peranan dalam Strategi Pemasaran Bisnis E-Commerce - WAHDATUN SANIA NASTI; Sofia Adra Zain; Adri Angga Harahap (Yayasan Literasi Emas Nusantara, 2025)
Management Information Systems (MIS) have become a vital component in supporting marketing strategies for e-commerce businesses. MIS enables companies to analyze customer data in real-time, allowing them to tailor marketing strategies to dynamic market trends. This study employed a literature review approach, examining various relevant sources, including scholarly journals, to analyze the role of MIS in e-commerce marketing. The results show that MIS enhances marketing effectiveness by enabling more accurate data-driven analytics, increasing personalization, and improving marketing budget efficiency. MIS also fosters innovation in marketing campaigns, especially through automation and adaptation to consumer needs. The challenges of implementing MIS primarily lie in the complexity of integration and organizational readiness. However, when properly implemented, MIS significantly enhances the competitiveness of e-commerce businesses